Design, optimization and simulation of a low‑voltage shunt capacitive RF‑MEMS switch - Ma, Li Ya; Nordin, Anis Nurashikin; Soin, Norhayati (Springer Berlin / Heidelberg, 2015)
This paper presents the design, optimization and simulation of a radio frequency (RF) micro-electromechanical system (MEMS) switch. The capacitive RF-MEMS switch is electrostatically actuated. The structure contains a coplanar waveguide, a big suspended membrane, four folded beams to support the membrane and four straight beams to provide the bias voltage. The switch is designed in standard 0.35 µm complementary metal oxide semiconductor process and has a very low pull-in voltage of 3.04 V. Taguchi method and weighted principal component analysis is employed to optimize the geometric parameters of the beams, in order to obtain a low spring constant, low pull-in voltage, and a robust design. The optimized parameters were obtained as w = 2.5 µm, L1 = 30 µm, L2 = 30 µm and L3 = 65 µm. The mechanical and electrical behaviours of the RF-MEMS switch were simulated by the finite element modeling in software of COMSOL Multiphysics 4.3® and IntelliSuite v8.7®. RF performance of the switch was obtained by simulation results, which are insertion loss of −5.65 dB and isolation of −24.38 dB at 40 GHz.